(untitled) (ResearchJet Journal of Analysis and Inventions, 2022)
The thesis aimed to prepare and apply educational units according to the strategy of active learning, according to Thelin model supported by hypermedia. The researcher used the experimental approach to suit the nature of the problem and the objectives of the research. The experimental approach is considered one of the best scientific research methods for solving problems in a practical way, which is defined as the objective observation of a specific phenomenon that occurs in a situation characterized by the exact accuracy of one or more variables. While the other variables (factors) are fixed. Where the researcher intentionally identified the research community from the students of the middle school of Ash-Shaheed Talib Al-Suhail for the distinguished students in the Directorate of Education of Baghdad Al-Karkh, the third for the academic year 2022-2023, whose number is 106 students. As for the research sample, it was chosen randomly and systematically (lottery), as it consisted of fifth grade preparatory students, with four divisions, Division A 35 students, Division B 35 students, Division C 34 students, and Division D 38 students. The systematic random method was used to determine the two research groups, as Division (A) was chosen to be an experimental group and Division (D) was a control group, and the lists of each group for research consisted of 16 students, and thus the research sample consisted of (32) students who constitute 40% of the research community. As this percentage is representative and real for the research community. The researcher conducted a pre-test for the skills under study, and educational units were implemented, at the rate of two units per week, the time of the unit was 45 minutes. After that, the post-test was conducted under the same conditions as the pre-test. The researcher used the spss statistical bag to obtain the results, which led the researcher to the conclusions that active learning according to Thelin’s model supported by hypermedia is considered as a collective investigation model that helps learners understand science positions and their interaction in the process of learning knowledge. Active learning according to Thelin’s model has a proportional and consistent effect and is based on a scientific and effective method, which led to the student gaining experience as a result of the model’s sequential and interrelated steps, increasing this experience and mastering knowledge. The recommendations are the most important interest in the strategy of active learning as an educational strategy in the lessons of physical education. Emphasis on benefiting from the positives of Thelin’s model in organizing the content of the instructional unit as a new output for the physical education lesson.